2011
DOI: 10.1163/cl-2011-040
|View full text |Cite
|
Sign up to set email alerts
|

The Nation Ex-Situ: On climate change, deterritorialized nationhood and the post-climate era

Abstract: It is plausible that the impacts of climate change will render certain nation-states uninhabitable before the close of the century. While this may be the fate of a small number of those nation-states most vulnerable to climate change, its implications for the evolution of statehood and international law in a “post-climate” regime is potentially seismic. I argue that to respond to the phenomenon of landless nationstates, international law could accommodate an entirely new category of international actors. I int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(27 citation statements)
references
References 1 publication
(1 reference statement)
0
26
0
1
Order By: Relevance
“…Finalmente, para el caso de los pequeños Estados insulares de escasa elevación, se ha de considerar que la elevación del nivel del mar trae como consecuencia la salinización de los acuíferos y la pérdida de territorio, junto con los efectos de tormentas cada vez más frecuentes e intensas, por lo que pueden resultar inhabitables en el corto plazo e incluso verse sumergidos en el largo plazo (Burkett, 2011). Esto plantea un sinnúmero de cuestiones nunca tratadas en el derecho internacional, pues no se había dado la situación de estar ante una posible "inhabitabilidad total" o "desaparición del Estado" por la elevación del nivel del mar (Gagain, 2012).…”
Section: Los Vacíos Jurídicos En El Derecho Internacional De Los Moviunclassified
“…Finalmente, para el caso de los pequeños Estados insulares de escasa elevación, se ha de considerar que la elevación del nivel del mar trae como consecuencia la salinización de los acuíferos y la pérdida de territorio, junto con los efectos de tormentas cada vez más frecuentes e intensas, por lo que pueden resultar inhabitables en el corto plazo e incluso verse sumergidos en el largo plazo (Burkett, 2011). Esto plantea un sinnúmero de cuestiones nunca tratadas en el derecho internacional, pues no se había dado la situación de estar ante una posible "inhabitabilidad total" o "desaparición del Estado" por la elevación del nivel del mar (Gagain, 2012).…”
Section: Los Vacíos Jurídicos En El Derecho Internacional De Los Moviunclassified
“…The nation ex situ is likewise another aspect of changing the doctrinal, traditional approach to territorialized state, in accordance with the Montevideo Convention. So-called deterritorialized states, outside their primary place of existence (ex situ) are able to maintain their heritage and remain an equal partner on the international arena, while not losing its indeed vital position as a sovereign state (Burkett, 2011;Rayfuse, 2010). Such new category of international personality would also need recognized international legitimacy.…”
Section: Propositionsmentioning
confidence: 99%
“…Discussions regarding the continuing existence of a State in the context of Atoll Island States have frequently assumed that having a territory is essential for the preservation of Statehood. It has been suggested that, as possible solutions for the disappearance of their territory, Atoll Island States could seek to acquire lands through cession of territory (Soons, ), that they build artificial islands and that the United Nations Convention on the Law of the Sea (UNCLOS) is amended in order to accept such islands as defined territories (Gagain, ), that they form a union with other States (Soons, , Caron, ) or even that they could become deterritorialized states (Rayfuse , Burkett, ). Among these suggestions, it seems that the States affected are currently trying to ensure that they eventually have a territory to resettle in.…”
Section: Atoll Island States and Territorial Lossmentioning
confidence: 99%